Catabolism and Deactivation of the Lipid-Derived Hormone Jasmonoyl-Isoleucine - Koo, Abraham J.; Howe, Gregg A. (Frontiers in Plant Science, 2012)
The oxylipin hormone jasmonate controls myriad processes involved in plant growth, development, and immune function. The discovery of jasmonoyl-l-isoleucine (JA-Ile) as the major bioactive form of the hormone highlights the need to understand biochemical and cell biological processes underlying JA-Ile homeostasis. Among the major metabolic control points governing the accumulation of JA-Ile in plant tissues are the availability of jasmonic acid, the immediate precursor of JA-Ile, and oxidative enzymes involved in catabolism and deactivation of the hormone. Recent studies indicate that JA-Ile turnover is mediated by a ω-oxidation pathway involving members of the CYP94 family of cytochromes P450. This discovery opens new opportunities to genetically manipulate JA-Ile levels for enhanced resistance to environmental stress, and further highlights ω-oxidation as a conserved pathway for catabolism of lipid-derived signals in plants and animals. Functional characterization of the full complement of CYP94 P450s promises to reveal new pathways for jasmonate metabolism and provide insight into the evolution of oxylipin signaling in land plants.